Aportes de la gestión ambiental a un modelo de sostenibilidad empresarial (2017)
The monograph studies how to include environmental management within the sustainability strategy of the business model. The permanence of companies in a market depends on their strategies, in other words the permanence of companies in a market, depend on their business strategies considering social, economic and environmental sustainability factors in their business model, this work must allow to identify the contributions that environmental management has to a business sustainability model, implies recognizing the real commitment of its managers with the structuring of strategies and objectives that are reflected in the mission and vision of the business, based on these factors and their interaction